2020
DOI: 10.3390/md19010002
|View full text |Cite
|
Sign up to set email alerts
|

The Remarkable Antioxidant and Anti-Inflammatory Potential of the Extracts of the Brown Alga Cystoseira amentacea var. stricta

Abstract: Inflammation and oxidative stress are part of the complex biological responses of body tissues to harmful stimuli. In recent years, due to the increased understanding that oxidative stress is implicated in several diseases, pharmaceutical industries have invested in the research and development of new antioxidant compounds, especially from marine environment sources. Marine seaweeds have shown the presence of many bioactive secondary metabolites, with great potentialities from both the nutraceutical and the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 57 publications
3
37
1
Order By: Relevance
“…Meroditerpenes were found in both extracts with the structures containing the chromane or quinone groups, such as: cystoketal quinone, demethylcystoketal chromane and cystoketal chromane, and/or cystoketal. The extracts showed a very low grade of toxicity on RAW 264.7 macrophages and L929 fibroblasts and a plethora of antioxidant and antiinflammatory effects [21]. The different efficacy of the two extracts in the various antioxidant and anti-inflammatory tests may be attributable to the quantitative, and not qualitative, difference of the present natural organic compounds.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Meroditerpenes were found in both extracts with the structures containing the chromane or quinone groups, such as: cystoketal quinone, demethylcystoketal chromane and cystoketal chromane, and/or cystoketal. The extracts showed a very low grade of toxicity on RAW 264.7 macrophages and L929 fibroblasts and a plethora of antioxidant and antiinflammatory effects [21]. The different efficacy of the two extracts in the various antioxidant and anti-inflammatory tests may be attributable to the quantitative, and not qualitative, difference of the present natural organic compounds.…”
Section: Introductionmentioning
confidence: 86%
“…In a biological screening it was demonstrated that 4 -methoxy-(2E)-bifurcarenone inhibits cell division, since it stops the development of the fertilized eggs of the common sea-urchin Paracentrotus lividus [20]. DMSO and 50%-ethanolic extracts from E. amentacea from the Ligurian Sea (northwestern Mediterranean) were obtained, and their bioactive properties were investigated [21]. Meroditerpenes were found in both extracts with the structures containing the chromane or quinone groups, such as: cystoketal quinone, demethylcystoketal chromane and cystoketal chromane, and/or cystoketal.…”
Section: Introductionmentioning
confidence: 99%
“…Both seaweeds showed similar DPPH and ABTS radical scavenging activity with C. crinita cold methanolic extract having IC 50 of 125.6 µg/mL and 254.8 µg/mL, respectively. De La Fuente et al [32] extracted C. amentacea var. stricta with dimethyl sulfoxide (DMSO) and 50% ethanol for determining TPC, TFC and antioxidant activity of extracts by DPPH radical scavenging, FRAP, OH scavenging, and nitric oxide (NO) scavenging methods.…”
Section: Total Phenolic Content Total Tannin Content and Antioxidant ...mentioning
confidence: 99%
“…In the last 5 years, several studies have been carried out with the aim of evaluating the bioactive properties of marine organisms. Several studies have tested the extracts and the isolated compounds from extracts of marine organisms for bioactivities [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], of which the cytotoxic activity [ 27 , 30 , 32 , 33 , 35 , 36 , 37 , 38 , 40 , 41 , 44 , 45 , 46 , 47 , 48 ] stands out. However, only in some studies was it possible to isolate the compounds and test them for cytotoxic activity [ 32 , 33 , 35 , 36 , 37 , 38 , 40 , 41 ].…”
Section: Secondary Metabolites From Marine Organisms With Cytotoxic Activitymentioning
confidence: 99%